Material analyses and field applications for the conservation of archeological remains found in the aerial cable car station construction site in Hatay (Türkiye) - Akbulut, Dilek Eksi; Uguryol, Mehmet; Haznedar, Burak (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2025)
During the constructions carried out within the scope of the Aerial Cable Car Project planned by Hatay Metropolitan Municipality, archaeological remains were discovered in & Idot;plik Pazar & imath; District where a station was going to be built, and upon that discovery, rescue excavation works were started in 2012 for the conservation of the remains. This article deliberates the material analyses of the archeological remains performed during the preparation of the survey, restitution, and restoration projects; the field inspections and the small-scale intervention trials on the remains carried out during the implementation phase of the cable car project; the suggestions developed for the conservation of the remains based on these studies, and the conservation practices carried out in line with these suggestions. In this context, the determined characteristics of the stone, brick, and mortar samples taken from the remains were given, recommendations for the consolidation mortar and injection grout compositions were presented, and the field applications carried out in line with these recommendations were outlined. Other conservation activities were also addressed, such as the methods used in the fight against algae formation on the wall surfaces and works conducted for repairing terracotta pipes and sarcophagi.
Keywords: Antioch; archaeological; injection grout; earthquake; material analysis; MORTARS; BYZANTINE; Architecture